Climate Conscious: Caribbean Commodities and Holdridge Life Zones, 1940s–1960s. - Lucier, Oliver (Isis: A Journal of the History of Science in Society, 2023)
During the 1980s and 1990s the Holdridge Life Zones system was one of the first and most influential ecological classifications used to predict the effects of climate change on vegetation worldwide. This was not its original purpose. This classification, first published in 1947 and revised in 1967, was explicitly designed to boost agricultural efficiency in the Greater Caribbean tropics. Leslie Holdridge, an American forester, developed his life zone scheme while leading extractive American scientific missions to procure Caribbean commodities like rubber and cinchona during World War II. Drawing on these experiences, he theorized that climate naturally shaped discrete ecological regions (life zones), which he believed were inherently suited to certain types of land use, such as the cultivation of particular tropical commodities. This essay thus argues that Holdridge Life Zones constructed climate as a normative force to prescribe efficient and sustainable land use throughout the Greater Caribbean. However, as later ecologists and biogeographers extended the Holdridge Life Zones classification to the global scale, this normativity was successfully erased. This essay thus investigates an overlooked and pioneering intersection of ecology and climate science, moving beyond formalized programs like the International Biological Program to reveal the centrality of resource extraction and the Greater Caribbean in shaping global bioclimatic knowledge.